Refrigerated storage of pork meat sprayed with rosemary extract and ascorbic acid - Perlo, Flavia Maria (2018)
There is an increasing consumer demand to avoid the use of synthetic additives like many antioxidants currently added to food. The objective of this study was to determine the effect of spraying ascorbic acid, rosemary extract and a combination of both on pork meat during refrigerated storage. Pork meat with antioxidants sprayed on the surface was packaged under vacuum and stored (4ºC, 45d). pH, color, lipid oxidation, total aerobic count, drip loss and moisture were evaluated during storage. Results suggested that surface application of rosemary extract and a combination of rosemary extract and ascorbic acid resulted in an effective delay of lipid oxidation of pork meat, without affecting pH, colour or water content during storage. No effect of rosemary extract on microbial growth was observed.